Kedudukan Hukum Wanita yang Mulih Daha di Banjar Munggu Kecamatan Mengwi Kabupaten Badung - Ni Komang Tri Intan Suaristiwayani; I Ketut Sukadana; Diah Gayatri Sudibya (Fakultas Hukum, Universitas Warmadewa, 2020)
For Balinese indigenous people, a woman returning to her parents’ home due to divorce has the status of mulih daha. With this status, a woman will have swadharma (obligations) and swadikara (rights) just like before the marriage took place in their respective homes. Several women who have experienced a mulih daha case have visited Banjar Munggu to regain their rights and carry out their obligations. This study examines the procedure for the return of a Balinese woman with the status of mulih daha and their customary position in Banjar Munggu Mengwi Badung. To achieve this goal, this research was conducted using an empirical legal research method with a sociological approach to law. Data were collected through selecting and summarising the data obtained from applicable legal provisions into relevant data with the object of the study. The results reveal that a woman with mulih daha status as a result of divorce does not have the right to inherit from her husband’s assets and / or that of their parents’, except from joint assets in inheritance. In Banjar Munggu Mengwi, the inheritance provisions for women with mulih daha status are clearly stipulated in the Awig-Awig of Banjar Adat, stipulating that every woman with the status of mulih daha is prohibited from joining in the village organisation.